Comparison between different protocols for DNA extraction for Hypostomus affinis - M. Rodrigues-Zeferino; S. Oliveira-Olimpio; P.C. Costa-Pierro; M. Fanttini-Polese; J.D. Souza-Neto; M. Moreira-Moulin; P. Pierro-Mendonça (Brazilian Journal of Biology)
Abstract The sand catfish or painted catfish (Hypostomus affinis) is a species native to Brazil and has some peculiar characteristics: a flattened body covered by bony plates and fins with spikes for fixing on rocks. Molecular studies have been carried out to better understand this and other species of fish. In this study, a comparison was made between DNA extraction methodologies to define the best extraction protocol for this species. For the study, approximately two grams of the caudal fin of twenty adult specimens of Hypostomus affinis were used for DNA extraction. For this, three extraction protocols were performed. The quantification of the genetic material was carried out in a NanoDrop 2000c Spectrophotometer, thus obtaining the DNA concentration in ng/µL and purity of each sample (A260/A280 and 230/260 ratio). Protocol I, based on Barrero, was the one that presented the best result of DNA concentration of 2846.28 ng/µL. Showing no difference from the III NaCL, which showed 2385.69 ng/µL of DNA. It is concluded that the protocol I presented the best results in terms of quantity and purity.